THE FUNCTIONS OF DISCOURSE MARKERS “OH” AND “WELL” USED IN (500) DAYS OF SUMMER MOVIE - Tirsa, Arvelia; Kurniawan, Yulius; Kurniawan, Yohanes (Universitas Widya Kartika Surabaya, 2023)
The purpose of this research is to avoid miscommunication and misunderstanding in communication between couple in a relationship. With discourse markers, it helps to minimize those from happening. This research especially investigates the functions of “Oh” as marker of information management and “Well” as marker of response in discourse markers. This research based on the theory of Discourse Markers by Deborah Schiffrin in 1987. Descriptive qualitative method applied in revealing the data by analyzing (500) Days of Summer movie. After collecting the data, the analysis began with classifying the data based on the functions, then categorizing the data by putting them in form of table, continue with identifying the role of “Oh” and “Well” as functions in discourse markers, to finish the research is by making conclusion from the findings. The findings indicate that there are ten functions of “Well” which are as delay marker, as ideational structure of answer, as ideational options, as contigent answer, as answer, as question, as repair initiation, as request, as compliance, and as turn initiator. There are also seven functions of “Oh” which are repairs initiation, as answer, acknowledgement of answer, as information receipt, as recognition display, and as question.